Peculiarities of the Conjugative pSa Plasmid Transfer from Escherichia coli into Francisella tularensis - A. N. Mokrievich; N. A. Shishkova; I. A. Dyatlov; V. M. Pavlov (Проблемы особо опасных инфекций, 2013)
per a recipient cell). pSa′ plasmid molds several topological shapes with variable electrophoretic mobility in E. coli C600, while in tularemia microbe, this plasmid has only one shape. After the transfer of the plasmid from E. coli cells into F. tularensis cells each individual clone of tularemia microbe possesses a plasmid which differs in its electrophoretic mobility from plasmids of other clones.